Browz : automatic visual regression testing using containers for Web apps running on Chrome and Firefox (2020)
Open source Javascript solution that explores inside a docker container a given web app and detects the differences across browsers with Visual Regression testing (with snapshot comparisons). In this regard, any software developer can analyze and/or visualize its results and take decisions on how to improve the given app